Performance Evaluation and Organization’s Culture Impactson Job Satisfaction and Employees’ Performance - Nurdjanah Hamid; Agus Yulianto; Amiruddin Amrullah; Siti Haerani (Hasanuddin Economics and Business Review, 2017)
Abstract:Thestudy investigatesand evaluates impactsof performance evaluation and company’s culture on job satisfaction and employees’ performance. Methodof data collection is using questionnaire. Data was analyzed by path analysis with decomposition model of causal influence between variables. The resultsindicate thatthe influence of two variables -performance evaluation and Company’s culture have direct and indirect effect to employees’ performance. The other variable (job satisfaction) has direct effect to employees’performance.